2021
DOI: 10.1097/md.0000000000025551
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protective effect of intracoronary administration of nicorandil and alprostadil via targeted perfusion microcatheter in patients undergoing elective percutaneous coronary intervention

Abstract: Background: The aim of the study was to evaluate the efficacy of nicorandil and alprostadil on myocardial protection in patients undergoing elective percutaneous coronary intervention (PCI). Methods: In this prospective, single-blinded, randomized controlled study, 90 consecutive patients scheduled for elective PCI for de novo coronary lesions were assigned to the nicorandil, alprostadil, and nitroglycerin groups in a 1:1:1 ratio. Drugs were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…A previous randomized controlled trial indicated that intracoronary administration of Nicorandil and PGE1 was more effective in improving myocardial perfusion than Nitroglycerin. 21 Another randomized-controlled study administered lipo-PGE1 at 20 µg/day diluted in 10 ml of NS through an intravenous injection over 5 min, starting at 3 days before PCI and continuing for 4 days after PCI. The results suggested that the cardioprotective effects of lipo-PGE1 were associated with its anti-inflammatory properties and its ability to improve microvascular perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…A previous randomized controlled trial indicated that intracoronary administration of Nicorandil and PGE1 was more effective in improving myocardial perfusion than Nitroglycerin. 21 Another randomized-controlled study administered lipo-PGE1 at 20 µg/day diluted in 10 ml of NS through an intravenous injection over 5 min, starting at 3 days before PCI and continuing for 4 days after PCI. The results suggested that the cardioprotective effects of lipo-PGE1 were associated with its anti-inflammatory properties and its ability to improve microvascular perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Nicorandil abolished homocysteine‐induced coronary MVO in mice [163]. It was reported that nicorandil reduced the incidence of MVO in patients with AMI and PCI [164–168].…”
Section: Katp Channels Collateral Blood Flow No‐reflow Phenomenon And...mentioning
confidence: 99%
“…Lipid microsphere nanoparticles encapsulating alprostadil have been widely utilized in the treatment of myocardial infarction, angina, and other cardiovascular diseases. Alprostadil exerts inhibitory effects on platelet aggregation, promotes vasodilation to enhance microcirculation, dilates coronary arteries, and increases myocardial perfusion [ 19 ]. A randomized controlled trial involving 300 patients with acute myocardial infarction (AMI) who underwent percutaneous coronary intervention (PCI) demonstrated that the combination of alprostadil and tanshinone IIa injection notably improved cardiac function and ventricular remodeling post-PCI, while also reducing the incidence of adverse events [ 20 ].…”
Section: Nanoparticle Classification In Cadmentioning
confidence: 99%